POLYMERIC COATING LIFE TIME UNDER VIBRO-LOADING - Vadim A. Kokhanovskiy; Vladilen V. Rubanov; Sergey I. Ivanov (Advanced Engineering Research)
The field research on the tribocoupling resource generation with the polymer composite coating from creep and wear under the subcritical vibro - loading is resulted.